2014
DOI: 10.1063/1.4896108
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity of microscale volumes of viscoelastic soft matter by cavitation rheometry

Abstract: Measurement of the elastic modulus of soft, viscoelastic liquids with cavitation rheometry is demonstrated for specimens as small as 1 ll by application of elasticity theory and experiments on semi-dilute polymer solutions. Cavitation rheometry is the extraction of the elastic modulus of a material, E, by measuring the pressure necessary to create a cavity within it [J. A. Zimberlin, N. Sanabria-DeLong, G. N. Tew, and A. J. Crosby, Soft Matter 3, 763-767 (2007)]. This paper extends cavitation rheometry in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Second, can we smooth out the singular uncharged p-branes in arbitrary dimensions? Using the generalization of chiral Born-Infeld theory [20] we found that the answer for both questions is positive.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Second, can we smooth out the singular uncharged p-branes in arbitrary dimensions? Using the generalization of chiral Born-Infeld theory [20] we found that the answer for both questions is positive.…”
Section: Introductionmentioning
confidence: 93%
“…Here we will review the theory of chiral Born-Infeld [20]. As in the Skyrme model [15] the chiral Born-Infeld theory can be conveniently formulated in terms of a chiral field U (t, x), a unitary 2 × 2 scalar matrix transforming under SU (2).…”
Section: Review Of Chiral Born-infeld Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…One way to stabilize it is by having higher order kinetic terms, as shown by Skyrme [8]. More recently scalar field theories with noncanonical kinetic terms have been extensively studied in [9,10] where it is shown that stable defects exist. In [11] we prove numerically that SO(N ) textures with Dirac-Born-Infeld (DBI) kinetic term can be stabilized in any arbitrary spatial dimensions N ≥ 3.…”
mentioning
confidence: 99%
“…Without loss of generality we can set β = 1 for simplicity 3. The case for N = 3 is discussed in[10].…”
mentioning
confidence: 99%